2020
DOI: 10.1038/s41598-020-71945-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased persistence of large-scale circulation regimes over Asia in the era of amplified Arctic warming, past and future

Abstract: Extreme weather events in Asia have been occurring with increasing frequency as the globe warms in response to rising concentrations of greenhouse gases. Many of these events arise from weather regimes that persist over a region for days or even weeks, resulting in disruptive heatwaves, droughts, flooding, snowfalls, and cold spells. We investigate changes in the persistence of large-scale weather systems through a pattern-recognition approach based on daily 500 hPa geopotential height anomalies over the Asian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 25 publications
2
24
0
Order By: Relevance
“…(While the f ‐test detected significant (>90%) trends in nodes #2 and #6, the number of LDEs is too small to be consequential). These findings are consistent with our earlier work on weather‐regime persistence (Francis et al., 2018, 2020; Vihma et al., 2019). Specifically, Francis et al.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…(While the f ‐test detected significant (>90%) trends in nodes #2 and #6, the number of LDEs is too small to be consequential). These findings are consistent with our earlier work on weather‐regime persistence (Francis et al., 2018, 2020; Vihma et al., 2019). Specifically, Francis et al.…”
Section: Resultssupporting
confidence: 93%
“…(While the f-test detected significant (>90%) trends in nodes #2 and #6, the number of LDEs is too small to be consequential). These findings are consistent with our earlier work on weather-regime persistence (Francis et al, 2018(Francis et al, , 2020Vihma et al, 2019). Specifically, Francis et al (2018) found an increased occurrence of LDEs, particularly in patterns featuring positive height anomalies in high latitudes of the North American domain, the same as that used in the present study.…”
Section: Observed Changes In Wwessupporting
confidence: 93%
See 2 more Smart Citations
“…Global climate change is causing more persistent weather in the midlatitudes (Coumou et al, 2018; Francis et al, 2020; Pfleiderer et al, 2019). Amplified arctic warming reduces the temperature difference with the equator, resulting in more sluggish circulation patterns and a “wavier” jet stream (Coumou et al, 2018; Mann et al, 2017).…”
Section: Introductionmentioning
confidence: 99%